Bone regeneration during osteoporosis: a translational in vivo monitoring of callus mechanical parameters - Toscano-Angulo, Juan J.; Mora-Macías, Juan; Blázquez-Carmona, Pablo; Sánchez-Raya, Manuel; Morgaz, Juan; Gómez-Galán, Juan Antonio; Granados, M. M.; Domínguez, Jaime; Reina-Romo, Esther (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionRegenerating osteoporotic bone remains challenging due to healing complications such as non-unions. Distraction osteogenesis is a promising technique for bone repair, but its efficacy under osteoporotic conditions is poorly understood. This study provides in vivo quantitative translational knowledge on the influence of osteoporosis in distraction callus mechanics.MethodsFifteen Merino sheep were induced with osteoporosis. A 15 mm bone defect in the right hind metatarsus was treated with distraction osteogenesis and stabilized with an instrumented external fixator. Callus distraction forces and relaxation were recorded and modeled to assess the viscoelastic behavior of the organic matrix. Callus ossification and mechanics were assessed using x-ray imaging and gait analysis. The results were compared to those from similar studies involving non-osteoporotic subjects.ResultsOsteoporosis significantly reduced distraction force peaks and relaxation (p < 0.05), with effects diminishing over the relaxation time. The elastic component of the organic matrix, especially ground substance, was significantly impaired (p < 0.05). X-ray follow-up and gait analysis revealed that half of the pathologic animals recovered comparably to non-osteoporotic subjects, while the others exhibit lateralized mineralization and reduced load bearing capacity.DiscussionOsteoporosis led to a 50% reduction in the viscoelastic response of the distraction callus, likely due to an impaired osteoblastic matrix synthesis. Furthermore, osteoporotic patients undergoing distraction osteogenesis for critical-size defects may experience delayed consolidation with heterogeneous mineralization, which may be linked to early deficits in organic matrix formation.